1986
DOI: 10.1159/000183805
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Exercise Training during Hemodialysis

Abstract: Fourteen maintenance hemodialysis patients volunteered to participate in a 6-month program of exercise training. The exercise was performed on a stationary bicycle during the hemodialysis treatment. Six maintenance hemodialysis patients served as control without exercise training. Exercising patients participated in 91% of all possible exercise sessions. The exercise group showed a significant (23%) increase in maximal oxygen consumption over the 6 months. No change in exercise capacity resulted in the control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
90
1
12

Year Published

1989
1989
2011
2011

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(111 citation statements)
references
References 7 publications
8
90
1
12
Order By: Relevance
“…Although the intensity and the duration of exercise in the studies varies, all have included initial moderate aerobic training progressing to vigorous training for 30 min or more three times per week for Ն8 wk up to 12 mo (most studies 3 to 6 mo). On average, aerobic exercise training for 8 wk to 6 mo improves VO 2peak by approximately 17% (Figure 3), but there is considerable variability from study to study, and many studies have been uncontrolled (16,18,30,(32)(33)(34)(35)(36)41,43). Only two of these studies included patients who were on peritoneal dialysis (35,40).…”
Section: Aerobic Exercise Trainingmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the intensity and the duration of exercise in the studies varies, all have included initial moderate aerobic training progressing to vigorous training for 30 min or more three times per week for Ն8 wk up to 12 mo (most studies 3 to 6 mo). On average, aerobic exercise training for 8 wk to 6 mo improves VO 2peak by approximately 17% (Figure 3), but there is considerable variability from study to study, and many studies have been uncontrolled (16,18,30,(32)(33)(34)(35)(36)41,43). Only two of these studies included patients who were on peritoneal dialysis (35,40).…”
Section: Aerobic Exercise Trainingmentioning
confidence: 99%
“…These other outcomes have included anemia, lipid levels, BP control, endothelial function, inflammation, mental health, and health-related quality of life. Although a few small studies have reported an improvement in anemia with vigorous aerobic exercise training (30,31), the majority of studies have not reported this benefit (32)(33)(34)36). Studies of the lipid effects of vigorous aerobic exercise training have also been mixed, with some showing a decrease in triglyceride (30,31) or an increase in HDL cholesterol (30,31) and others not showing any changes (34 -36).…”
Section: Aerobic Exercise Trainingmentioning
confidence: 99%
See 1 more Smart Citation
“…Improvements in HD patients' physical fitness as measured by reaction time and lower extremity muscle strength (16), left ventricular systolic function (17), and psychosocial functioning (18) have been demonstrated in randomized clinical trials. Other studies of exercise interventions in patients who were on HD have provided evidence to support improvement in arterial stiffness (19), decrease in pulse pressure (20), increase in aerobic capacity (21)(22)(23)(24)(25)(26), reduced need for antihypertensive medications (23,27,28), increase in hemoglobin concentration and hematocrit levels (28), and improved lipid metabolism (28). Started HD in hospital-based facility (%) 29.6 a CABG, coronary artery bypass grafting; HD, hemodialysis; AMI, acute myocardial infarction; COPD, chronic obstructive pulmonary disease.…”
Section: Discussionmentioning
confidence: 99%
“…70 Although probably unrealistic, it has been recommended that people exercise in a controlled environment where they can be closely monitored secondary to systemic and cardiac complications. One study by Painter et al 71 showed positive results when individuals ride a stationary bike and exercise during their dialysis treatment.…”
Section: Exercise Prescriptionmentioning
confidence: 99%